GAMBARAN PROMOSI KESEHATAN TENTANG KESEHATAN REPRODUKSI PADA REMAJA DI SMP MUHAMMADIYAH 1 DELI SERDANG - NURHASANAH SYM (JURNAL ILMIAH KOHESI, 2019)
The highest number of sexual violence against women and children in North Sumatra was in the Deli Serdang area of 116 women (Dinkes, 2015). At Deli Serdang Muhammadiyah 1 Junior High School there are still reproductive health problems such as courtship at the time of examination in class, courtship at home is empty, and there are incidents of pregnancies outside of marriage. In junior high school health promotion only uses media such as leaflets, PPT (Power Point), and usually uses the lecture method. The description of health promotion on reproductive health in adolescents shows good, namely 66 respondents (56.4%). In media health promotion that is used well, namely 64 respondents (54.7%), the method used is good, namely 62 respondents (53.0%), the material provided is quite good, namely 61 respondents (52.1%), enough speakers / instructors both, namely 58 respondents (49.6%), and institutions in good health promotion, namely 72 respondents (61.5%). The description of health promotion on reproductive health in adolescents in the good category as many as 66 respondents (56.4%). In media health promotion that is used well, namely 64 respondents (54.7%), the method used is good, namely 62 respondents (53.0%), the material provided is quite good, namely 61 respondents (52.1%), enough speakers / instructors both, namely 58 respondents (49.6%), and institutions in good health promotion, namely 72 respondents (61.5%).